Analysis of the Cochrane Review: Thrombolysis for Acute Deep Vein Thrombosis. Cochrane Database Syst Rev. 2014,1: CD002783. - Sousa Nanji, Liliana (2015)
The standard treatment for acute deep vein thrombosis (DVT) targets to reduce immediate complications, however thrombolysis could reduce the long-term complications of post-thrombotic syndrome in the affected limb. This systematic review aimed to assess the effects of thrombolytic therapy and anticoagulation versus anticoagulation in people with deep vein thrombosis of the lower limb through the effects on pulmonary embolism, recurrent deep vein thrombosis, major bleeding, post-thrombotic complications, venous patency and venous function. The Cochrane Peripheral Vascular Diseases Group Trials Search Co-ordinator searched the Specialised Register (last search in April 2013) and CENTRAL (2013, Issue 4). A total of 17 randomised controlled trials (RCTs) and 1103 participants were included. In the experimental group receiving thrombolysis, complete clot lysis occurred more frequently and there was greater improvement in venous patency. The incidence of post-thrombotic syndrome decreased by a 1/3 and venous ulcers were less frequent. There were more bleeding complications and 3 strokes occurred in less recent studies, yet there seemed to be no significant effect on mortality. Data on the occurrence of pulmonary embolism and recurrent deep vein thrombosis were inconclusive. There are advantages to thrombolysis, yet the application of rigorous criteria is warranted to reduce bleeding complications. Catheter-directed thrombolysis is the current preferred method, as opposed to systemic thrombolysis in the past, and other studies comparing these procedures show that results are similar.Keywords: Randomized Controlled Trials as Topic; Thrombolytic Therapy; Venous Thrombosis.